Piketty’s Inequality between the Profit and Growth Rates and Its Implications for the Reproduction of Economic Elites - Sánchez, Alberto Benítez (Scientific Research, 2016)
This paper studies, within a growth model, some effects of the inequality between the profit and growth rates on the reproduction of economic elites. To this end, it considers as functions of the capital/income ratio the relations between, on the one hand, the economic growth rate and, on the other hand, the growth rates of capital and of national income. Based on this, it shows that when the income of a particular socio-economic stratum increases with respect to the national income, the lower limit for the growth rate of the first income depends almost exclusively on the variations of the capital/income ratio and of the average productivity of labor, while the employment growth rate plays a secondary role. Moreover, the paper distinguishes between three categories of renter and establishes sufficient conditions for the reproduction of each one of them. It points out that the third category, which comprises those renter dynasties whose share in the national capital stock increases with each generation, constitutes a quasi-feudal development within capitalist societies.
Keywords: Economic Elites; Income Inequality; Piketty; Renter Dynasties; Sraffa